1996
DOI: 10.1063/1.1146886
|View full text |Cite
|
Sign up to set email alerts
|

Gas temperature in a hot filament diamond chemical vapor deposition system

Abstract: The gas temperature in a hot filament activated diamond chemical vapor deposition system is derived from the vacuum ultraviolet absorption spectrum of the H2 molecule. Curves of growth for the optically thick spectra are calculated using a Voigt line shape and published oscillator strengths in order to measure relative populations of H2 in various rotational and vibrational levels of the ground electronic state. The H2 vibrational levels are nearly in equilibrium. The gas temperature field is most strongly inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The sensitivity of CARS is low and the spatial resolution is limited, unless BOXCARS or folded BOXCARS arrangements are employed, but absolute calibration is possible since it is easy to detect H 2 ( v = 0). Vibrationally excited H 2 can be detected by LIF,161, 163 and absorption spectroscopy 93, 163, 164, 171. With these techniques, however, it is impossible to detect H 2 (v = 0), and hence to evaluate the H 2 ( v = 1)/H 2 ( v = 0) population ratio without using short‐wavelength radiation below the LiF cut‐off.…”
Section: Production and Detection Of Vibrationally Excited H2 Molementioning
confidence: 99%
“…The sensitivity of CARS is low and the spatial resolution is limited, unless BOXCARS or folded BOXCARS arrangements are employed, but absolute calibration is possible since it is easy to detect H 2 ( v = 0). Vibrationally excited H 2 can be detected by LIF,161, 163 and absorption spectroscopy 93, 163, 164, 171. With these techniques, however, it is impossible to detect H 2 (v = 0), and hence to evaluate the H 2 ( v = 1)/H 2 ( v = 0) population ratio without using short‐wavelength radiation below the LiF cut‐off.…”
Section: Production and Detection Of Vibrationally Excited H2 Molementioning
confidence: 99%
“…Although precise conversion of column density to mole fraction is difficult due to uncertainties in the gas temperature field, an estimate can be made using a local gas temperature of 1100 K as measured by Menningen et al in an identical reactor. 5 Such a temperature yields a C 6 H 6 mole fraction of approximately 1ϫ10 Ϫ6 for our conditions. Our experimental measurement of gas phase C 6 H 6 is four orders of magnitude higher than that predicted from kinetics modeling.…”
Section: Resultsmentioning
confidence: 76%
“…Detailed gas phase temperature studies in this system have shown that the substrate temperature dominates the gas temperature field, except in the nearfilament region. 5 Although single-color optical pyrometry has its limitations, particularly when used to measure the temperature of a filament with an emissivity changing during carbonization, the bulk gas phase chemistry and C 6 H 6 formation in particular, is largely unaffected by modest inconsistencies in filament temperature due to inaccuracies in filament temperature measurement. Total gas flow is maintained at 100 sccm using mass flow controllers and an exhaust throttle valve holds the chamber pressure at 20 Torr.…”
Section: Introductionmentioning
confidence: 99%
“…This sudden change is likely not the cause of the ∼100 K temperature drop just past the filament that has been measured experimentally in FACVD chambers. [42][43][44][45][46] Instead, the change happens in our calculations because the initial concentration distribution of the feed gas is an artificial mixture and not a natural state for the system. Figure 6a suggests that the system kinetics allows the initial gas mixture to adjust itself quickly to adapt to a new environment.…”
Section: Iv1 Ab Initio Ratementioning
confidence: 99%